2020
DOI: 10.1002/joc.6638
|View full text |Cite
|
Sign up to set email alerts
|

Identifying hotspots cities vulnerable to climate change in Pakistan under CMIP5 climate projections

Abstract: In this study, an ensemble of statistically downscaled 14 multi-global climate models for RCP4.5 and RCP8.5 emission scenarios was employed to implement a comprehensive assessment of climate change impacts over Pakistan in order to identify the future hotspots cities in terms of changes in temperature and precipitation. The analyses focused on the minimum, maximum and average temperature and precipitation in three time-slices: 2006-2035, 2041-2070, and 2071-2,100. Average temperature is projected to increase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…A combination of increased surface albedo [7], cloud radiative forcing, e.g., [75], and soil moisture feedbacks can (at least partly) explain a more significant T min warming within the UIB. A projected increase in WS precipitation, which is robust across many studies, e.g., [40,63,76], further supports such feedbacks. Since the WS precipitation mostly falls as snow, increased albedo from the fresh snow surface (and associated cloud covers) may largely explain a smaller increase in T max .…”
Section: Ws Projectionssupporting
confidence: 55%
See 3 more Smart Citations
“…A combination of increased surface albedo [7], cloud radiative forcing, e.g., [75], and soil moisture feedbacks can (at least partly) explain a more significant T min warming within the UIB. A projected increase in WS precipitation, which is robust across many studies, e.g., [40,63,76], further supports such feedbacks. Since the WS precipitation mostly falls as snow, increased albedo from the fresh snow surface (and associated cloud covers) may largely explain a smaller increase in T max .…”
Section: Ws Projectionssupporting
confidence: 55%
“…Moreover, the magnitude of projected warming differs significantly among different studies. For instance, a recent study projected about 6 • C warmer UIB [40], but nearly half of this warming is reported by [41] under similar radiative forcing. Considering greater sensitivities of the Indus flows towards warming magnitude, where 1 • C rise in the mean temperature can increase up to 16% glacial flows [42], such warming discrepancies can seriously implicate the adaptation planning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, our ensemble also includes their secondary considerations for Dry-Warm (CMCC-CMS) and Wet-Cold (CNRM-CM5) regional future (see Table 2). Similarly, the 14-model CMIP5 ensemble of Ali et al (2020) also contains almost all our models. Such ensemble similarities justify the regional relevance of our models, despite its smaller sample size.…”
Section: Diversity Of the Gcm Ensemblementioning
confidence: 99%